Inovasi Manajemen Humas Untuk Meningkatkan Daya Saing Lembaga Pendidikan - Rahmah Salsabila, Naila; Bedi, Fisman; Amalia Fitri, Tin (Indonesian Journal of Islamic Educational Management, 2024)
Public relations management includes an important posture on the success of a learning institution. In Madrasah Tsanawiyah (MTs), innovation in public relations management is important in the face of modern occupation and globalization, if not more familiar to the rhythm of public occupation. The purpose of this study is to examine how innovation in public relations management can improve the competitiveness of learning institutions. This research focused on MTs Rawa Selapan using case study as the design and descriptive qualitative methodology. The principal, public relations, vice principal for curriculum and vice principal for student affairs, became the researcher's resource persons. The analysis technique in this study used Miles and Huberman analysis, namely by data reduction, data presentation, conclusion drawing/verification. The results of this study indicate that MTs Rawa Selapan's innovative strategy in managing public relations contributes to increasing competitiveness. Through creative public relations strategies, MTs Rawa Selapan can improve its image in the community, increase social media followers, and improve the standard of education offered by the institution. Percieve assesses MTs Rawa Selapan from the trusted community, as a result of these innovations to open a wider network while increasing relevance